Lacrimal System Endoscopy Assisted Endonasal Dacryocystorhinostomy. (June 2013) - Kim, Charles; Kacker, Ashutosh; Levine, Benjamin; Lelli, Gary J.
Abstract Objective: To assess the potential benefit of intra-operative lacrimal system endoscopy during endonasal dacryocystorhinostomy. Methods: Eight patients (10 cases) underwent lacrimal system endoscopy assisted endonasal dacryocystorhinostomy for nasolacrimal duct obstruction between May 2010 and July 2012 at the New York Presbyterian Hospital/Weill Cornell Medical College. All patients were subsequently followed post-operatively for at least 6 months. Primary outcome measures included post-operative epiphora and infection. Results: Lacrimal system endoscopy assisted endonasal dacryocystorhinostomy was successful in identifying the level of nasolacrimal duct obstruction in all 10 cases. Endoscopy revealed obstruction at the valve of Hasner in 2 cases, while the remaining cases involved obstruction at more proximal locations within the nasolacrimal duct. The location of the rhinostomy created during dacryocystorhinostomy was tailored to the specific level of obstruction. No intra-operative complications were encountered. The majority of patients (6 of 8) experienced complete resolution of epiphora within 1 month of surgery, with all patients achieving resolution by 6 months. None of the patients in the study exhibited any signs of post-operative dacryocystitis. Conclusion: The evaluation and management of nasolacrimal duct obstruction may be greatly enhanced through the use of intra-operative lacrimal system endoscopy by specifically localizing and identifying the underlying cause of obstruction, while maintaining the excellent success rate of endonasal dacryocystorhinostomy.